Onset of fast magnetic reconnection via subcritical bifurcation - Guo, Zhibin; Wang, Xiaogang (Frontiers in Physics, 2015)
We report a phase transition model for the onset of fast magnetic reconnection. By investigating the joint dynamics of streaming instability(i.e., current driven ion acoustic in this paper) and current gradient driven whistler wave {\color{blue} {prior to the onset of fast reconnection}}, we show that the nonlinear evolution of current sheet(CS) can be described by a Landau-Ginzburg equation. The phase transition from slow reconnection to fast reconnection occurs at a critical thickness, $Δ_c\simeq \frac{2}{\sqrt{π}}\left|\frac{v_{the}}{v_c}\right|d_e$, where $v_{the}$ is electron thermal velocity and $v_c$ is the velocity threshold of the streaming instability. For current driven ion acoustic, $Δ_c$ is $≤10d_e$. If the thickness of the CS is narrower than $Δ_c$, the CS subcritically bifurcates into a rough state, which facilitates breakage of the CS, and consequently initiates fast reconnection.